Casearia sylvestris Essential Oil Degradation Products Generated by Leaf Processing - Carvalho, Flávio A. [UNESP]; Oda, Fernando B. [UNESP]; Crevelin, Eduardo J.; Crotti, Antônio E. M.; dos Santos, André G. [UNESP] (Wiley, 2021)
Casearia sylvestris is an endemic tree of the Latin America that the essential oil (EO) has anti-inflammatory and gastroprotective actions. This study evaluates the chemical composition of the EO from the volatile fractions of in natura, fresh, and dried C. sylvestris var. sylvestris and var. lingua leaves. For both varieties, the dried leaves presented higher EO yield as compared to fresh leaves. The major EO chemical components were (E)-caryophyllene, α-humulene, germacrene D, bicyclogermacrene, spathulenol, caryophyllene oxide, and humulene epoxide II. In both varieties, the content of sesquiterpene hydrocarbons decreased and oxygenated sesquiterpenes increased on going from in natura to fresh and dried leaves, which indicated that leaf drying and hydrodistillation modified the volatile composition. The results also suggested that bicyclogermacrene and (E)-caryophyllene were oxidized during processing, to generate spathulenol and caryophyllene oxide, respectively. C. sylvestris varieties and in natura, fresh, and dried leaves differed in terms of the chemical composition of volatiles, which could affect the EO biological activities.
Keywords: Casearia sylvestris var. sylvestris; essential oil; oxidation; thermal desorption; var. lingua